A Study on the Comparative Diagnostic Performance of Polymerase Chain Reaction, Rapid Diagnostic Technique and Microscopy in the three Northern Local Government Area of Taraba State, Nigeria - Chibuzor Obiorah Sylvester; Allahnanan Emmanuel; Peace Christopher Njideka; Chukwuebuka Igboaka Duke (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study is conducted to compare diagnostic performance of Polymerase Chain Reaction, Rapid Diagnostic Techniqu`e and Microscopy. Nested PCR, RDT and Microscopy methods were used to screen for P. falciparum in the study populations. From site Jalingo, 85(75.9%), 70(62.5%) and 97(86.6%) samples were positive using nested PCR, RDT and Microscopy, while 27(24.1%), 42(37.5%) and 15(13.4%) were negative respectively. For site Zing, 85(73.3%) were positive for PCR, while 31(26.7%) were negative; 81(69.8) were positive for RDT and 35(30.1) were negative, while 104(89.7%) were positive with Microscopy and 12(10.3%) negative. Also, 82(75.2%), 50(45.9%) and 103(94.5%) were positive respectively for nested PCR, RDT and Microscopy, while 27(24.8%), 59(54.9%) and 6(5.5%) were negative respectively for the methods from site Lau. In all, microscopy method record the highest number of positive samples. The number of True Positive (TP) and True Negative (TN) recorded are 85 and 11 for PCR and 75 and 5 for Microscopy in Jalingo, 85 and 14 for PCR and 77 and 4 for Microscopy in Zing and 82 and 9 for PCR and 82 and 6 for Microscopy in Lau. The specificity and sensitivity of RDT from Jalingo, Zing and Lau are respectively 47.8% & 95.5%, 51.8% & 95.5% and 50.0% & 96.9%. Also, the specificity and sensitivity of Microscopy are 18.55% & 88.2%, 12.9% & 90.6% and 22.2% and 100% respectively. Owing to the higher sensitivity of the PCR method compared to Microscopy and RDT, P. falciparum detection by PCR was used as the reference method. From study site Jalingo, 22 (19.6%) and 5 (4.5%) false positive results Microscopy and RDT were negative for PCR and 10 (4.5%) and 20 (9.0%) false negatives Microscopy and RDT. This shows that Microscopy has a four-fold false positive detection error rate than RDT, while RDT has a two-fold false negative detection error rate. 56 (50%) were positive for the three methods. From study site Zing, the number of false positive for Microscopy and RDT are respectively 27 (23.3%) and 8 (6.9%), while PCR corrected that were false negatives were 8 (6.9%) and 12 (10.3%) respectively. Also from site Lau, 21 (19.3%) false positives were recorded for Microscopy, while only 2 (1.8%) were recorded for RDT. Microscopy had 0 (0%) false negatives while RDT has 34 (31.2%) that were nested PCR corrected. The same trend in the number of false positives and false negatives was observed in all the three sites, while Microscopy generally has higher false positive rate, RDT has a higher false negative rate. This study underscores the clinical utility of hematological and biochemical parameters in malaria management, particularly in resource-limited settings like Nigeria. The findings highlight the importance of comprehensive diagnostic approaches and suggest integrating these adjunct tools into malaria treatment protocols to enhance patient care and outcomes.